Numerical investigation of side arm gas volume fraction in two phase T-junction - Saieed, A. (Universiti Malaysia Pahang, 2016)
T-junction is commonly installed at the offshore production header as a separator to tap produced gas for downstream process operation. A major issue in the T-junction is the liquid carryover, where excessive liquid flows into the downstream process equipment causing the platform to trip. The primary objective of the present study is to determine the effect of ratio of side arm to main arm diameters on passive separation performance in T-junction. The analysis was carried out using Eulerian Multiphase model from ANSYS Fluent 16.1. The boundary conditions chosen for the inlet and two outlets of the T-junction were velocity inlet and volume fraction outlet flow, respectively. Likewise, pressure velocity coupling was achieved by using SIMPLE coupling scheme. Three different side to main arm diameter ratio and side to main arm length ratio of 0.2, 0.6, and 1.0 were investigated, with different gas velocities variation and inlet gas saturation. Investigation found that the gas volume fraction in the side arm cannot go beyond 90 irrespective of the variation of parameters such as gas to liquid velocity ratio, diameter ratio, length ratio, and mass split ratio. It was found that the amount of gas exiting through the side arm decreases by decreasing the initial gas saturation and gas to liquid velocity ratio. However, by decreasing the mass split ratio, more gas ends up in side arm. Likewise, in terms of geometrical aspects, increasing the T-junction diameter ratio and reducing the length ratio causes an increase in extraction of gas into side arm. It was also noticed that the highest fraction of gas in side arm was achieved when the diameter ratio was 0.6. Therefore, it can be said that maximum amount of gas can be received in side arm when diameter ratio is around 0.6, initial gas saturation and velocity ratio are high, and mass split ratio is small. This paper discusses some of the most important parameters that are involved in partial phase separation in a T-junction. In order to have a more overall insight of the phase separation phenomena, it is required to explore the effects of inlet and outlet pressures, surface roughness of the pipe interior, angle between side and run arm, curvature radius at the junction, and the viscosity of the operating fluids. Â© Universiti Malaysia Pahang.